Case study and review article: epilepsy-like movements induced by fentanyl analgesia - Mahmoud El-Karamany (SpringerOpen, 2017)
Epilepsy-like movements are observed immediately after the administration of fentanyl as well as its derivatives. Although the event has no serious outcomes, it is so worrisome that it has garnered the attention of many authors to publish case reports of such events. Despite the presence of cerebral lesions in some cases, epileptic focus cannot be attributed to such lesions. Radiological and electrophysiological studies have failed to reveal abnormal cerebral activity during such events. The reported activity is usually generalized tonic-clonic convulsions. Epileptic convulsive movements were observed with low doses of fentanyl and its derivatives. Previous studies on animals have supported the occurrence of such epileptiform movements in corresponding doses. Idiosyncrasy and narcotic-related muscle rigidity did not satisfactorily explain the seizures. Our case report represents the occurrence of epileptiform movements twice in and an old patient with no cerebral insult. The past history was epileptic activity under control with lamotrigine for last 2 years.